2023
DOI: 10.1101/2023.06.06.543831
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motile bacteria leverage bioconvection for eco-physiological benefits in a natural aquatic environment

Abstract: Bioconvection, the active self-sustaining transport phenomenon triggered by the accumulation of motile microbes under competing physico-chemical cues, has been long studied, with recent reports suggesting its role in driving ecologically-relevant fluid flows. Yet, how this collective behaviour impacts the ecophysiology of swimming microbes remains unexplored. Here, through physicochemical profiles and physiological characterizations analysis of the permanently stratified meromictic Lake Cadagno, we characteriz… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 105 publications
0
3
1
Order By: Relevance
“…4C), contrary to what is usually observed (Fig. 4B) 22,34 . This situation also has an effect on the whole trophic network of Lake Cadagno, given the higher biovolume (Fig.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…4C), contrary to what is usually observed (Fig. 4B) 22,34 . This situation also has an effect on the whole trophic network of Lake Cadagno, given the higher biovolume (Fig.…”
Section: Discussioncontrasting
confidence: 84%
“…Previous studies, often conducted over one or a few days of sampling, have generally reported a certain regularity in the shift from a strong presence of large cells PSB C. okenii in early summer to an increase in the other phenotypic groups, namely small cells PSB and two GSB species in September 22,23,34,35 . While this pattern was evident in 2019, distinct ecological dynamics were observed in 2020 and 2021 (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations